Doing Rawls justice: Evidence from the PSID - Antonio Abatemarco (Kiel Institute for the World Economy (IfW), 2016)
Distributive value judgments based on the 'origins' of economic inequalities (e.g. circumstances and responsible choices) are increasingly evoked to argue that 'the worst form of inequality is to try to make unequal things equal'. However, one may reasonably agree that distributive value judgments should also account for the 'consequences' of economic inequalities in such a way as to (i) improve economic efficiency and (ii) prevent from subordination, exploitation and humiliation. In this way of thinking, by resorting the well-known Rawlsian 'fair equality of opportunity' and 'difference principle', the author proposes a pragmatical non-parametric estimation strategy to compare income distributions in terms of Rawlsian inequity and its contribution to overall inequality. The latter methodology is applied to PSID data from 1999 to 2013 and compared with existing empirical evidences on Roemer's (A Pragmatic Theory of Responsibility for the Egalitarian Planner, 1993, and Equality of Opportunity, 1998) inequality of opportunity. Remarkably, Rawlsian inequity is found between 56% and 65% of the overall income inequality, with an increasing pattern originating from the recent economic crisis.
Keywords: D63; I32; D3; 330; Rawlsian justice; equality of opportunity; income distribution